2022
DOI: 10.1186/s10195-022-00643-w
|View full text |Cite
|
Sign up to set email alerts
|

Management of femoral head fracture by Ganz surgical dislocation of the hip

Abstract: Introduction Posterior hip dislocation is the commonest type of hip dislocation. It is associated with femoral head fracture in 7% of cases. Urgent and congruent hip reduction is mandatory to improve clinical outcomes and avoid irreversible complications. The purpose of this study is to assess the safety and functional and radiological outcomes of surgical hip dislocation by Ganz technique for treatment of femoral head fracture. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hosny, H et al (2022) 10 showed open reduction and internal fixation of femoral head fracture using surgical hip dislocation through Ganz approach is a viable treatment option and provides satisfactory results with low complication rates.…”
Section: Resultsmentioning
confidence: 99%
“…Hosny, H et al (2022) 10 showed open reduction and internal fixation of femoral head fracture using surgical hip dislocation through Ganz approach is a viable treatment option and provides satisfactory results with low complication rates.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, complications such as heterotopic ossification and avascular necrosis were found to occur in 43% and 23% of patients, respectively, and femoral head fractures were treated with open reduction and internal fixation without surgical hip dislocation [6]. Hosny et al [3] proposed using the Ganz surgical hip dislocation technique for Pipkin Type I and II femoral head fractures, which led to only 1 in 18 patients having avascular necrosis at 2-year follow-up. Future research may demonstrate that the Ganz technique is most useful for Pipkin I femoral head fractures but not Pipkin IV femoral head fractures.…”
mentioning
confidence: 99%